Pengaruh Konsentrasi Seng Oksida (ZnO) dan Penambahan Gliserol terhadap Karakteristik Bioplastik dari Pati Umbi Gadung (Dioscorea hispida Deenst) - Saputra, Wijaya; Hartiati, Amna; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 4 (2019): DesemberDO - 10.24843/JRMA.2019.v07.i04.p05, 2019)
Bioplastics are a type of plastic made from renewable materials such as starch . A study aims to determine the effect of addition zinc oxide (ZnO) and the of glycerol and this interaction to the characteristics of the bioplastik starch dioscorea hispida and determine the addition of zinc oxide (ZnO) and the of glycerol to produce bioplastiks from starch dioscorea hispida with the best characteristics. This study uses factorial randomized block design. The first factor is the addition of zinc oxide (ZnO) which consists of 3 levels, namely 8, 9 and 10% (from 6 grams of starch). The second factor is the addition of glycerol which consists of 3 levels, namely 1; 1.5 and 2 grams. Each treatment is grouped into 2 based on production time, so that 18 units are obtained. The variables observed were tensile strength, elongation at break, elasticity, biodegradation, water absorption, water vapor transmission rate. The data obtained were analyzed for diversity and continued with a test of Significant Honest Difference. The results showed that the addition of zinc oxide and the glycerol have a very significant effect on tensile strength, elongation at break, elasticity, development and transmission of water vapor. While the interaction of the concentration of zinc oxide (ZnO) and the addition of glycerol have a very significant effect on tensile strength and elongation at break and have a significant effect on elasticity and development. The treatment of 10% addition with 1 gram of glycerol is the best characteristic of bioplastic dioscorea hispida denst with a tensile strength value of 1.385 ± 0.007 MPa ; e longation 10.2±0.014 % ; elasticity 13.995±0.204 M P a ; swelling 13.5±0.007 % ; Water Vapour T ransmition 0.0053 ± 0,013 g/ hour .m 2 ; biodegradation ability of 7 days. Keywords : bioplastics, ZnO, glycerol, D ioscorea hispida Deenst.